2016
DOI: 10.1590/2237-6089-2015-0081
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 and IL-10 levels in the umbilical cord blood of newborns with a history of crack/cocaine exposure in utero: a comparative study

Abstract: IL-6 and IL-10 might be early biomarkers of PCE in newborns. These findings could help to elucidate neurobiological pathways underlying neurodevelopmental changes and broaden the range of possibilities for early intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
0
6
1
3
Order By: Relevance
“…The results show innumerous negative outcomes for newborn health. Concerning the common physiological outcomes, low birth weight (Aghamohammadi & Zafari, 2016;Bateman, Ng, Hansen, & Heagarty, 1993;Behnke et al, 2001;Bender et al, 1995;R Cherukuri, Minkoff, Feldman, A, & Glass, 1988;Radha Cherukuri, Howard, Parekh, Feldman, & Glass, 1987;Fiocchi & Kingree, 2001;Leblanc, 1987;Mardini et al, 2016Mardini et al, , 2017Parcianello et al, 2018;Sprauve, Lindsay Michael K., Herbert, & Graves, 1997;Zavaschi et al, 2014) preterm delivery (Aghamohammadi & Zafari, 2016;Bateman et al, 1993;Behnke et al, 2001;R Cherukuri et al, 1988;Radha Cherukuri et al, 1987;Eyler et al, 1998;Fiocchi & Kingree, 2001;Leblanc, 1987;Reis & Loureiro, 2015;Sprauve et al, 1997;Xavier et al, 2017) and small for gestational age (Behnke et al, 2001;Leblanc, 1987;Reis & Loureiro, 2015) were well establish risk between newborn exposure to crack cocaine during pregnancy (dos Santos et al, 2018). The low 5-minute Apgar score (Parcianello et al, 2018;Sprauve et al, 1997) and small head circunference (Behnke et al, 2001;R Cherukuri et al, 1988;Radha Cherukuri et al, 1987;Leblanc, 1987) were also reported as a risk to crack cocaine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The results show innumerous negative outcomes for newborn health. Concerning the common physiological outcomes, low birth weight (Aghamohammadi & Zafari, 2016;Bateman, Ng, Hansen, & Heagarty, 1993;Behnke et al, 2001;Bender et al, 1995;R Cherukuri, Minkoff, Feldman, A, & Glass, 1988;Radha Cherukuri, Howard, Parekh, Feldman, & Glass, 1987;Fiocchi & Kingree, 2001;Leblanc, 1987;Mardini et al, 2016Mardini et al, , 2017Parcianello et al, 2018;Sprauve, Lindsay Michael K., Herbert, & Graves, 1997;Zavaschi et al, 2014) preterm delivery (Aghamohammadi & Zafari, 2016;Bateman et al, 1993;Behnke et al, 2001;R Cherukuri et al, 1988;Radha Cherukuri et al, 1987;Eyler et al, 1998;Fiocchi & Kingree, 2001;Leblanc, 1987;Reis & Loureiro, 2015;Sprauve et al, 1997;Xavier et al, 2017) and small for gestational age (Behnke et al, 2001;Leblanc, 1987;Reis & Loureiro, 2015) were well establish risk between newborn exposure to crack cocaine during pregnancy (dos Santos et al, 2018). The low 5-minute Apgar score (Parcianello et al, 2018;Sprauve et al, 1997) and small head circunference (Behnke et al, 2001;R Cherukuri et al, 1988;Radha Cherukuri et al, 1987;Leblanc, 1987) were also reported as a risk to crack cocaine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A exposição pré-natal à cocaína também está associada a alterações neurocomportamentais durante a infância e a adolescência. A dependência de cocaína gera um estado de estresse crônico e a manutenção desse estresse provoca mudanças no equilíbrio das citocinas (MARDINI et al, 2016).…”
Section: )unclassified
“…O estresse crônico leva à ativação do eixo hipotalâmicopituitário -adrenal, eixo do sistema nervoso simpático e fibras do nervo vago, provocando a secreção de glicocorticóides, catecolaminas e acetilcolina, perturbando a homeostase das citocinas. As IL-6 e IL-10 podem ser biomarcadores precoces da exposição pré-natal a cocaína em recém-nascidos (MARDINI et al, 2016). Esses resultados podem ajudar a elucidar as vias neurobiológicas subjacentes a alterações do desenvolvimento e aumentar a gama de possibilidades para intervenção precoce.…”
Section: )unclassified
See 1 more Smart Citation
“…Clinical Studies. Newborns whose mothers used crack or cocaine during pregnancy have elevated inflammation in umbilical cord blood compared to control children, even after adjusting for maternal psychopathology, sociodemographic factors, and nicotine consumption ( Mardini et al, 2016 ). Maternal alcohol consumption during pregnancy increases the risk for infection during early childhood due to alcohol-induced reductions in immune responses to antigens ( Pasala et al, 2015 ).…”
Section: Hpa Axis and The Immune Systemmentioning
confidence: 99%